2019
DOI: 10.1088/1755-1315/270/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Local Rice Genotypes of Tana Toraja and North Toraja Regencies: Kinship Relations and Character Interaction

Abstract: Tree, The Regency of Tana Toraja and North Toraja, are two regencies in the Province of South Sulawesi where even though both are not the center of rice crop development, but in both regencies we can find many cultivated local rice genotypes. This study aims to determine the relationship between local rice genotypes found in the two regencies based on panicle and grain characteristics and the correlation between these characters. The characters observed are panicle length, grains number per panicle, panicle de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Similarly, Amboupe et al ( 2019) reported that the Bentong tribe in Baru district, South Sulawesi, relied on rice and maize as staple foods when settled, and kenrang fruit (Ficus racemosa) and sikapa tubers (Dioscorea hispida) during their nomadic phase, with an ICS value of 100 for rice. The high ICS value of rice is attributable to its multifaceted benefits for the Toraja people, serving as a staple food, raw material for cake preparation (including traditional Dori cakes), medicine, and an integral component of traditional ceremonies (Riadi et al, 2019;Ranteallo et al, 2020;Helida et al, 2015). As stated by Barumbun et Al.…”
Section: Plant Cultural Significance Of the Toraja Tribe In South Sul...mentioning
confidence: 99%
“…Similarly, Amboupe et al ( 2019) reported that the Bentong tribe in Baru district, South Sulawesi, relied on rice and maize as staple foods when settled, and kenrang fruit (Ficus racemosa) and sikapa tubers (Dioscorea hispida) during their nomadic phase, with an ICS value of 100 for rice. The high ICS value of rice is attributable to its multifaceted benefits for the Toraja people, serving as a staple food, raw material for cake preparation (including traditional Dori cakes), medicine, and an integral component of traditional ceremonies (Riadi et al, 2019;Ranteallo et al, 2020;Helida et al, 2015). As stated by Barumbun et Al.…”
Section: Plant Cultural Significance Of the Toraja Tribe In South Sul...mentioning
confidence: 99%
“…The advantages of specific environmental adaptation and quality possessed by local black rice, this rice has weaknesses in terms of deep harvesting age and relatively lower production when compared to national superior varieties. Pare Ambo has a harvest age of 135-140 days after sowing with an average production of 5 tons per hectare, while Pare Lallodo has a harvest age of 150-160 days after sowing with a production of 5.8 tons per hectare [7].…”
Section: Introductionmentioning
confidence: 99%
“…Local upland rice that has been introduced and has been registered at the Plant Variety Protection Agency of the Ministry of Agriculture and most of them are in South Sulawesi, West Sumatra and Central Java [9]. Among the several local rice that have been registered, there are also five Toaraja local rice namely Pare Ambo, Pare Bau, Pare Kombong, Pare Lallodo and Pare Lea [10]. The five local rice have long been adapted and cultivated by local farmers in the Toraja highlands at an average altitude of 700-2000 m above sea level [11].…”
Section: Introductionmentioning
confidence: 99%